PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) BERBANTU VIDEO ANIMASI TERHADAP HASIL BELAJAR IPAS SISWA KELAS V SD NEGERI KALIBANTENG KIDUL 02 SEMARANG - Setiya Wigati, Yuli; Afandi, Muhamad; Solikhun, Muhamad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low understanding of student concepts which impacts the minimal learning outcomes of science. The Problem Based Learning learning model assisted by animated videos emphasizes student activeness in problem-solving learning with the help of animated video media. The Problem Based Learning learning model is very important because it increases student critical involvement in finding solutions to material problems, so that they are able to understand the material concepts in depth which has an impact on improving learning outcomes. The study aims to determine the effectiveness of the Problem Based Learning learning model in improving the learning outcomes of fifth-grade students of SD Negeri Kalibanteng Kidul 02 West Semarang. Sampling used a purposive sampling technique, with a sample of 25 students in the experimental class and 26 students in the control class. Data collection with a written test of 20 items. Data analysis includes normality test, homogeneity test and hypothesis test which are processed with the help of SPSS version 23. The results of the study indicate that there is an effectiveness of the PBL learning model assisted by animated videos in improving the learning outcomes of science in grade V students of SDN Kalibanteng Kidul 02, proven by a pretest value of 71.20 and a posttest value of 89.40 with a difference in increase of 18.20. There is a difference in the effectiveness of the PBL learning model assisted by animated videos with conventional learning in improving the learning outcomes of science, which is shown by the difference in the average posttest value of the experimental class of 89.40 and the control class of 79.81 with a difference of 9.59.